A systematic review of outcome reporting in incisional hernia surgery. Issue 2 (11th April 2021) - Harji, D; Thomas, C; Antoniou, S A; Chandraratan, H; Griffiths, B; Henniford, B T; Horgan, L; Köckerling, F; López-Cano, M; Massey, L; Miserez, M; Montgomery, A; et al.
Abstract: Background: The incidence of incisional hernia is up to 20 per cent after abdominal surgery. The management of patients with incisional hernia can be complex with an array of techniques and meshes available. Ensuring consistency in reporting outcomes across studies on incisional hernia is important and will enable appropriate interpretation, comparison and data synthesis across a range of clinical and operative treatment strategies. Methods: Literature searches were performed in MEDLINE and EMBASE (from 1 January 2010 to 31 December 2019) and the Cochrane Central Register of Controlled Trials. All studies documenting clinical and patient-reported outcomes for incisional hernia were included. Results: In total, 1340 studies were screened, of which 92 were included, reporting outcomes on 12 292 patients undergoing incisional hernia repair. Eight broad-based outcome domains were identified, including patient and clinical demographics, hernia-related symptoms, hernia morphology, recurrent incisional hernia, operative variables, postoperative variables, follow-up and patient-reported outcomes. Clinical outcomes such as hernia recurrence rates were reported in 80 studies (87 per cent). A total of nine different definitions for detecting hernia recurrence were identified. Patient-reported outcomes were reported in 31 studies (34 per cent), with 18 different assessment measures used. Conclusions: This review demonstrates the significant heterogeneity in outcome reporting in incisional hernia studies, with significant variation in outcome assessment and definitions. This is coupled with significant under-reporting of patient-reported outcomes. Abstract : This systematic review identifies the current clinical and patient-reported outcomes reported in the literature for incisional hernia.